If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -1x + -4 = 0 Reorder the terms: -4 + -3x + -1x = 0 Combine like terms: -3x + -1x = -4x -4 + -4x = 0 Solving -4 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -4x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = 0 + 4 -4x = 0 + 4 Combine like terms: 0 + 4 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| -6(x+3)-9=3x-9(x-5) | | -3x(-x-4)=0 | | 38-[5+6y-3(y+3)]=-3(5y-4)-[7(y-1)-10y+4] | | 5=a*5+b | | 2y+3=48 | | 8(x-5)=(-7)+2x | | (x+x)(5)= | | 4x^2-9y^2-24x+54y-189=0 | | -72-8y=72 | | 38-21=x-7 | | 11.3+x-8.1=3.6 | | 34=2x+16 | | f(x)=5x+6 | | -2x-3(-17)=-7 | | 30x^2+93x+72=0 | | -2x-3+(-17)=-7 | | 2x+5(2x-6)=-16-2x | | x/4=5/3 | | 5x^2-13x+6=(5x-3)(ax+-b) | | -21=-14t | | 2(5c-1)-2=7c+2 | | 30+x=18 | | 16x-17=-59 | | m(x-2)=m^2-2x | | 14x-(6x+4)=3x+5(x-1)+1 | | (5x+8)(5x+8)=36 | | 12cos(x)-5sin(x)=0 | | 80=x+x+x+2.5X+2.5X | | 4y+3y=16 | | 1/7(y+7)=2y | | x*1=0.97 | | 2a+3a-6a-7=21+a+4 |